(untitled) (Bangladesh Journal of Microbiology, 2008)
A total of 32 mortality cases of captive animals at the Dhaka Zoo due to various infections was detected and reconfirmed at two reference laboratories in Bangladesh during the period February 2000 to February 2006. Among the 22 different animal species studied, highest incidence was observed with gaur (15.6%), followed by spotted deer (12.5%), rhesus macaque (9.4%), common pea fowl (6.2%) and others (56.3%). A total 35 isolates belonging to six different genera was recovered from the diseased animals. Among the pathogens, Mycobacterium spp. was the most prevalent (27.8%), which was followed by Coccidioides immitis (19.4%), Escherichia coli (19.4%), Salmonella spp. (13.9%), Staphylococcus spp. (13.9%), and Aspergillus spp. (5.6%). Mycobacterium spp. and C. immitis showed the widest range of host susceptibility. Establishment of a standard microbiological laboratory at the Dhaka Zoo is necessary for early diagnosis of threatening infections among valuable captive animals in order to improve animal health as well as to reduce the morbidity rate. Keywords: Mortality, Animal pathogens, Confirmatory diagnosis, Tuberculosis, Coccidioidomycosis DOI: http://dx.doi.org/10.3329/bjm.v24i2.1263